Synthesis of the Proposed Structure of Cryptoconcatone H - Csókás, Dániel; Bates, Roderick W. (Synlett, 2019)
A synthesis of the proposed structure of cryptoconcatone H and one diastereoisomer has been achieved, featuring a tandem deprotection–oxa-Michael addition to establish the tetrahydropyran moiety. Comparison of the NMR spectroscopic data confirms that the original structural assignment was incorrect.
Keywords: tetrahydropyran; Michael addition; metathesis; stereochemistry; tandem reaction